Penyuluhan Program Stop Bullying dalam Mengatasi Perundungan di SDN Rengasdengklok Selatan III Kabupaten Karawang - Widiastuti, Hesti; Humairoh, Siti; Indah Mutiara, Imas (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2026)
his study aims to improve the competence of junior high school teachers. Bullying in elementary schools is a serious problem that requires comprehensive and systematic handling. This community service program aims to implement a stop bullying program at SDN Rengasdengklok Selatan III, Karawang Regency, through interactive counseling activities and the installation of anti-bullying campaign posters. The methods used included interactive lectures, educational video screenings, group discussions, and singing activities with the theme of stopping bullying. The target of the activity was 18 fifth-grade students who were actively involved in the program during three meetings. The results of the activity showed an increase in students' understanding of the definition, types, and effects of bullying, as well as the creation of collective awareness to prevent bullying in the school environment. This program produced anti-bullying posters that were displayed in various corners of the school as visual reminders for the entire school community.